Adoption of a Newly Launched Software Product in the Market by Innovation Diffusion Modelling - Anchal Anchal; Arunava Majumder; Pardeep Goel; Manoj Singh Adhikari (Operations Research and Decisions)
The growing significance of software upgrades is one of the most intriguing and pertinent market trends of the last few years. Fierce competition on a worldwide scale combined with the ever-changing environment has rendered software products outdated. During a program's early stages, increasing efforts are made to increase overall performance before its inherent performance limit is reached. To characterize the process of awareness, appraisal, and decision-making, mathematical models with step structures are presented. The first step is to present a system of ordinary differential equations that includes both the awareness and decision-making stages. Furthermore, it is demonstrated that if the adoption rate is strongly nonlinear, then although there exists a stable equilibrium, it is not a global attractor. It is shown that the system has bifurcation points. The direction of equilibrium bifurcation is also explored. (original abstract)